2015
DOI: 10.1039/c5cp05055c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence emissions of imide compounds and end-capped polyimides enhanced by intramolecular double hydrogen bonds

Abstract: The structure and optical properties of a newly synthesized imide compound (DHNHPI) that forms intramolecular double hydrogen bonds (intra-HBs) were investigated. This compound exhibits intense absorption at 372 nm (ε = 5091 cm(-1) M(-1)) and strong emission at 427 nm (Φ = 0.507) in CHCl3. Under basic conditions, the absorption and fluorescence peaks showed large bathochromic shifts by 70 nm and 95 nm, respectively, compared with the neutral condition due to conversion to anion form. Based on the single-crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…Data from fluorescence spectroscopy of CHCA3 and CHCA4 also argue for the formation of ring–ring π‐interaction in CHCA3 but not in CHCA4. A ring–ring π‐interaction leads to a stacking of the ring that often results in a red‐shifted emission . Steady state fluorescence spectra of CHCA3 showed emission at 466 nm, which is red‐shifted compared with that of CHCA4, which has an emission peak at 443 nm (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from fluorescence spectroscopy of CHCA3 and CHCA4 also argue for the formation of ring–ring π‐interaction in CHCA3 but not in CHCA4. A ring–ring π‐interaction leads to a stacking of the ring that often results in a red‐shifted emission . Steady state fluorescence spectra of CHCA3 showed emission at 466 nm, which is red‐shifted compared with that of CHCA4, which has an emission peak at 443 nm (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…A ring-ring π-interaction leads to a stacking of the ring that often results in a red-shifted emission. [30][31][32] Steady state fluorescence spectra of CHCA3 showed emission at 466 nm, which is red-shifted compared with that of CHCA4, which has an emission peak at 443 nm ( Figure S2). This suggests that ring-ring π-stacking between CHCA3 molecules exists and is more extensive than that between CHCA4 molecues.…”
Section: π-Stacking Interactionsmentioning
confidence: 99%
“…The weakening of the acidity of the urea N-H moiety at 9 position of anthracene might be induced by the electron-donating ureaÁÁÁAcO À moiety located at 10 position. Furthermore, 3,6-dihydroxy-N-cyclohexylphthalimide (DHNHPI), which has two symmetrically placed intramolecular proton transfer sites, also shows a resonance effect to avoid the ESIPT mechanism in the excited state (38). This resonance effect may play an important role in the occurrence of the ESIPT reaction.…”
Section: Interaction Between 910btdspua and Tbaac In The Excited Statementioning
confidence: 99%
“…They found that the HBs endowed imide compounds and polyimides with enhanced fluorescence properties as well as high sensitivity towards pH. [40] Cheng et al have designed and synthesized a series of Salen ligands, combined with two intramolecular HBs and different nonconjugated alkyl bridges ((CH 2 ) n , n = 2-9, 12; cyclohexyl). [41] It can be confirmed that these Salen ligands should be used in mechanofluorochromism (crystal defect-induced emission) and living cell imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Kanosue and Ando have synthesized novel imide compound 3,6‐Dihydroxy‐N‐cyclohexylphthalimide (DHNHPI) containing two intramolecular HBs. They found that the HBs endowed imide compounds and polyimides with enhanced fluorescence properties as well as high sensitivity towards pH . Cheng et al have designed and synthesized a series of Salen ligands, combined with two intramolecular HBs and different nonconjugated alkyl bridges ((CH 2 ) n , n = 2‐9, 12; cyclohexyl) .…”
Section: Introductionmentioning
confidence: 99%